Efficacy of clozapine versus standard treatment in adult individuals with intellectual disability and treatment-resistant psychosis (CLOZAID): study protocol of a multicenter randomized clinical trial - Alemany-Navarro, María; Sánchez-Barbero, Bianca; Reguera-Pozuelo, Pablo; Altea-Manzano, Laura; Gómez-Garrido, Ana; Rocha-González, Idalino; Garrido-Torres, Nathalia; Ruiz-Veguilla, Miguel; García-Cerro, Susana; Rosso-Fernández, Clara M.; Villagrán-Moreno, José María; Sarramea, Fernando; et al. (Frontiers in Psychiatry, 2024)
Intellectual disability (ID) affects approximately 1% of the worldwide population and individuals with ID have a higher comorbidity with mental illness, and specifically psychotic disorders. Unfortunately, among individuals with ID, limited research has been conducted since ID individuals are usually excluded from mental illness epidemiological studies and clinical trials. Here we perform a clinical trial to investigate the effectiveness of clozapine in the treatment of resistant psychosis in individuals with ID. The article highlights the complexity of diagnosing and treating psychopathological alterations associated with ID and advocates for more rigorous research in this field.A Phase IIB, open-label, randomised, multicentre clinical trial (NCT04529226) is currently ongoing to assess the efficacy of oral clozapine in individuals diagnosed with ID and suffering from treatment-resistant psychosis. We aim to recruit one-hundred and fourteen individuals (N=114) with ID and resistant psychosis, who will be randomised to TAU (treatment as usual) and treatment-with-clozapine conditions. As secondary outcomes, changes in other clinical scales (PANSS and SANS) and the improvement in functionality, assessed through changes in the Euro-QoL-5D-5L were assessed. The main outcome variables will be analyzed using generalized linear mixed models (GLMM), assessing the effects of status variable (TAU vs. Clozapine), time, and the interaction between them.